If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n6=5(n-2)
We move all terms to the left:
n6-(5(n-2))=0
We add all the numbers together, and all the variables
n^6-(5(n-2))=0
We calculate terms in parentheses: -(5(n-2)), so:We do not support enpression: n^6
5(n-2)
We multiply parentheses
5n-10
Back to the equation:
-(5n-10)
| 29=9+5x | | 5y/3-2=2y+1 | | 2=23-3h | | 6+9+d=d | | 15=-6m+4-1 | | 9.49+0.3h=-4.62-8h | | 40+6x+3x+5=180 | | 4,465=47(p+30) | | 7g+23=58 | | x+20+2x=56 | | 5y÷3-2=2y+1 | | 7(n-5)=-7+(-11) | | m-2.9=-1.4 | | 38=y-46 | | 36+2v=74 | | 3n-4=4n-6 | | 4×+y=18 | | 6p-13=29 | | 3(×+2=2(x+5) | | 15x=+3=48 | | 7k-32=53 | | 34+w=56 | | mF=180 | | 2x=2(2)^3 | | 46+2d=92 | | 12a-18=11a+3 | | 4=x32 | | 11+8y=35 | | mA=180 | | 5+7(4x-2)=2-4(7x-6) | | 8+5h=43 | | 7x-10-x=2(x+1) |